Evaluating The Role Of Water Quality In Diarrheal Disease Prevalence: A Case Study From Al-Kadhimiya And Al-Amiriya, Baghdad (International Journal of Environmental Sciences, 2025)
This study examined the relationship between drinking water quality and diarrheal infections, with a particular focus on Entamoeba histolytica in Baghdad Province, Iraq. A total of 200 stool samples from diarrheal patients were microscopically examined for parasitic forms, while 36 drinking water samples were collected from Al-Kadhimiya and Al-Amiriya and analyzed for key physico-chemical parameters, including pH, electrical conductivity (EC), total dissolved solids (TDS), total hardness (T.H), calcium (Ca²⁺), magnesium (Mg²⁺), and chloride (Cl⁻).Findings revealed significant temporal and spatial variations in water quality, particularly elevated EC, TDS, and T.H levels by February 2025. Strong correlations were observed between T.H and Mg²⁺, and between EC and TDS, suggesting ionic contributions to water chemistry. Epidemiological data demonstrated a statistically significant link between E. histolytica infection and diarrhea prevalence. Notably, the prevalence of E. histolytica cysts showed a strong correlation with Cl⁻ concentrations, indicating potential fecal contamination. Additionally, elevated TDS and Mg²⁺ levels were associated with increased diarrheal incidence, possibly due to their gastrointestinal effects.The results highlight the importance of routine water quality monitoring and integrated public health interventions to mitigate the burden of waterborne diseases in urban environments.